2021
DOI: 10.1111/adj.12878
|View full text |Cite
|
Sign up to set email alerts
|

Management of dental emergencies amongst Australian general medical practitioners – A case‐vignette study

Abstract: Background In Australia, because of inequity in dental service accessibility and affordability, patients can see general medical practitioners (GPs) for acute dental conditions. Methods This cross‐sectional study consisted of surveys distributed to the board registered GPs practising in Australia. The main outcome measures included statistical analysis of GPs managing different dental emergency scenarios and their confidence and expectations in managing dental emergencies. Results A total of 425 GPs participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, multiple studies have shown that GPs tend to prescribe antibiotics as treatment for dental conditions (Anderson et al 2000;Cope et al 2015;Nguyen et al 2023). An Australian case-vignette study of 30 GPs who worked in rural Queensland, Tasmania and South Australia between 2013 and 2014 showed that GPs tend to prescribe antibiotics and short-term pain relief for dental conditions, including toothaches, dental abscesses and acute orofacial pain (Park et al 2022). Furthermore, they reported that costs of travelling to the dentist also discouraged patients from seeking dental care.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple studies have shown that GPs tend to prescribe antibiotics as treatment for dental conditions (Anderson et al 2000;Cope et al 2015;Nguyen et al 2023). An Australian case-vignette study of 30 GPs who worked in rural Queensland, Tasmania and South Australia between 2013 and 2014 showed that GPs tend to prescribe antibiotics and short-term pain relief for dental conditions, including toothaches, dental abscesses and acute orofacial pain (Park et al 2022). Furthermore, they reported that costs of travelling to the dentist also discouraged patients from seeking dental care.…”
Section: Introductionmentioning
confidence: 99%